Acute shortening and angulation for limb salvage in a paediatric patient with a high-energy blast injury. (20th March 2014) - Pikkel, Yoav Yechezkel; Wilson, Jessica Jeanne; Kassis, Shokrey; Lerner, Alexander
Abstract : We present the case of an 8-year-old girl casualty of the Syrian conflict who arrived with open fractures of the right tibia and fibula with extensive bone and soft tissue loss as well as an open fracture of the left calcaneus as the result of a high-energy blast injury. She was successfully treated with repeated debridement procedures, external fixation with acute temporary shortening and angulation of the right leg and skin grafting to both lower limbs.